IMPACT OF INCREASING POPULATION GROWTH IN GREATER GWALIOR ON HUMAN HEALTH: (WITH SPECIAL REFERENCE TO ENVIRONMENTAL DEGRADATION): बृहत्तर ग्वालियर में बढ़ती जनसंख्या वृद्धि का मानव स्वास्थ्य पर प्रभाव: (पर्यावरण अवनयन के विशेष सन्दर्भ में) - Parashar, Divya (International Journal of Research -GRANTHAALAYAH, 2015)
A person is always looking for suitable means of income to fulfill his basic needs. This is why cities started expanding when rural people migrated to cities. As a result, the cities which were settled in the past in the past, those cities settled in disorganized form in modern times and started taking the form of disorganized metros. This chaos in cities and metros has created pollution problem in front of us. Cities that are considered centers of civilization and culture have now become centers of pollution. व्यक्ति को सदा से ही अपनी मूलभूत आवश्यकताओं की पूर्ति के लिए आय के उचित साधनों की तलाश रहती है। यही कारण है कि ग्रामीण व्यक्तियों ने जब शहरों की ओर पलायन किया तो नगरों का विस्तार होने लगा। परिणाम स्वरूप पूर्व में जो नगर व्यवस्थित रूप से बसे हुऐ थे वहीं वे नगर आधुनिक समय में अव्यवस्थित रूप में बस कर अव्यवस्थित महानगरों का रूप लेने लगे। नगरों एवं महानगरों की इसी अव्यवस्था ने हमारे समक्ष प्रदूषण की समस्या खड़ी कर दी है। जो नगर सभ्यता व संस्कृति के केन्द्र माने जाते हैं अब वही नगर प्रदूषण के केन्द्र बन गये है।